An Overview of Life Gratitude on Ex-Prisoner Adolescents - Paula K. W. K. Lado; Marselino K. P. Abdi Keraf; Apris A. Adu; Indra Yohanes Kiling (Journal of Health and Behavioral Science, 2021)
Adolescence is a very important and critical part of an individual's development. This is because, in the stages of adolescent development, it is often marked by an identity crisis which causes an adolescent to be very vulnerable to conduct behavior that is not following prevailing norms and rules, such as deviant behavior. Adolescents who are found guilty according to the applicable law will be placed and fostered at the Special Development Institution for Children (LPKA) and referred to as Correctional Students (Andikpas). After serving a criminal period, adolescent ex-prisoner will come out and live again in society. However, this is not easy due to environmental resistance and the difficulty of carrying out social reintegration. On the other hand, this brings its lessons for adolescent ex-prisoners so that they can be grateful by seeing life more positively. This paper will discuss the different and unique overview of life gratitude of ex-prisoner adolescents. The discussion is hoped to be able to provide knowledge related to the gratitude of life and adolescent ex-prisoners.